Opportunity and risk in achieving food production and conservation goals at high altitude: Evidence from the Tibetan Plateau - Lijing Wang; Stephen Polasky; Fei Lu; Colleen R. Miller; Lingxiao Ying; Yi Xiao; Zhiyun Ouyang (Proceedings of the National Academy of Sciences, 2026)
The Tibetan Plateau, the Earth’s highest and largest plateau, has a harsh environment for agriculture, and is a global biodiversity hotspot, raising the challenge of simultaneously satisfying food production and conservation goals. Currently, agriculture involves crop production on steep slopes and overgrazing, which threatens future productivity. The Tibetan Plateau is also undergoing climate change. We evaluate food production from 1990 to 2020 and use these results to model future trends and risks to food production on the Tibetan Plateau. We assess the feasibility of achieving both food production and conservation goals simultaneously under climate change scenarios. Food production increased 32.33% over three decades, providing 2,892.98 kcal d −1 cap −1 , more than enough to satisfy food self-sufficiency. Under climate change, the Tibetan Plateau will become warmer and wetter under Shared Socioeconomic Pathways (SSPs) SSP126, SSP245, and SSP585, which combined with agricultural advances (e.g., improved mechanization and irrigation), will likely result in increased yields even with a 10% reduction in cropland area—greater than the total area of all steeply sloping cropland, thereby allowing retirement of steeply sloping cropland and livestock reductions while still meeting food production goals. Meanwhile, key ecosystem services, including carbon sequestration, water retention, and habitat quality, are also projected to improve substantially. Nonetheless, the increasing frequency and severity of extreme weather events are expected to reduce food production, undermine current dietary requirements and may threaten the minimum nutritional intake required for humans.